ANALISIS PELAKSANAAN PROGRAM KONVERGENSI STUNTING DI KABUPATEN ROKAN HULU TAHUN 2021 - Rosalia; Priwahyuni, Yuyun; Mitra, Mitra (LPPM Hang Tuah Pekanbaru, 2025)
Convergence is an approach to delivering interventions that are coordinated, integrated, and jointly delivered to prevent stunting for priority targets. The implementation of stunting convergence in Rokan Hulu Regency began in 2018. This study aims to analyze the implementation of the stunting convergence program in Rokan Hulu Regency in 2021. This is a qualitative study with a rapid assessment procedure research design.The research informants consisted of the main informants, namely from Bappeda, the Health Office, the Head of the Stunting Locus Health Center, and the Stunting Locus Village Head. Supporting informants are DP3AKB, Department of Public Works, Department of Education, Department of Food Security, and Department of Fisheries and Marine Affairs. Data analysis was carried out by transcribing, analyzing, and forming a matrix of research results, then triangulating the data. The results showed that the human resources in charge of monitoring nutrition at the Stunting Locus Health Center were not all trained. The budget for stunting convergence was from the APBD and the APBN and was considered to have been right on target and in accordance with the budgeting needs given. Facilities and infrastructure tend to be inadequate to implement the stunting convergence program. In the implementation of 8 stunting convergence actions, it was found that every action had been carried out, even though there were constraints in human resources, internet network availability, data availability, and suitability. It was recommended to the Rokan Hulu Government to increase the capacity of human resource managers, complete facilities and infrastructure, and improve coordination between managers of the stunting convergence program.